A Microeconomic Theory–Based Latent Class Multiple Discrete–Continuous Choice Model of Time Use and Goods Consumption. Issue 1 (2017) - Astroza, Sebastian; Pinjari, Abdul Rawoof; Bhat, Chandra R.; Jara-Díaz, Sergio R.
A microeconomic theory–based multiple discrete–continuous choice model was developed to accommodate ( a ) both time allocation and goods consumption as decision variables in the utility function, ( b ) both time and money budget constraints governing the activity participation and goods consumption decisions, ( c ) a finite probability of zero consumption and zero time allocation (i.e., corner solutions), and ( d ) technical constraints in the form of minimum consumption levels for any good that would be consumed and minimum time allocation for any activity conducted. The proposed model was applied in the form of a latent class model (to consider heterogeneity) on a Dutch data set to understand the determinants of weekly time use and goods consumption behavior.